ANALISIS DAN EVALUASI SIFAT KIMIA TANAH PADA LAHAN TEMBAKAU VARIETAS KEMLOKO DI SENTRA TEMBAKAU KABUPATEN TEMANGGUNG, JAWA TENGAH - Ainur Rofik; S Sudarto; D Djajadi (Jurnal Tanah dan Sumberdaya Lahan, 2019)
This study aimed to analyze the effect of soil chemical consisting of pH, C-organic, CEC, and base saturation on the production and quality index of Kemloko tobacco varieties, and to identify distribution map of soil chemical properties. The study was conducted by field survey and analysis spatial was used Inverse Distance Weighted interpolation method. The results showed that distribution of soil chemical properties in Tobacco Centers at the Temangung Regency consisting of acidic pH value with a range of values 3,96-6,97, soil C-organic ranges low with a range of values 0,19-6,79%, soil CEC ranges from high to very high with a range of values 10,98-67,84 me/100g-1, and low base saturation categories with a range of values 13,24-82,77%. Correlation coefficient obtained between the soil chemical properties and tobacco’s production; each of them is sequential, i.e., 0,112, -0,204, 0,005, -0,027 in the weak to very weak category. While the level of coefficient correlation between soil chemical properties and tobacco quality index, each of them is sequential, i.e. -0,001, -0,141, -0,175, 0,165 in the very weak category. This was because productivity and quality index of Kemloko tobacco varieties in Tobacco Centers at the Temanggung Regency on 2016 planted season due to high rainfall occurring throughout 2016 on the tobacco processing phase.